2022
DOI: 10.1542/peds.2021-054260
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk SARS-CoV-2 Antibodies up to 6 Months After Vaccination

Abstract: BACKGROUND: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–specific antibodies have been detected in human milk up to 6 weeks post–coronavirus disease 2019 (COVID-19) vaccination. We evaluated SARS-CoV-2-specific antibodies, neutralization activity, effect of pasteurization, and persistence through 6 months after vaccination. METHODS: This prospective longitudinal study enrolled 30 pregnant or lactating women. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Measurement of human milk IgG, IgA, and IgM antibodies targeting the SARS CoV-2 receptor binding domain (RBD) within the spike protein was performed using a modified enzyme-linked immunosorbent assay (ELISA) technique ( 6 , 23 ). In brief, to remove cells and fat, thawed human milk samples were centrifuged at 1,000 G for 10 min twice.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Measurement of human milk IgG, IgA, and IgM antibodies targeting the SARS CoV-2 receptor binding domain (RBD) within the spike protein was performed using a modified enzyme-linked immunosorbent assay (ELISA) technique ( 6 , 23 ). In brief, to remove cells and fat, thawed human milk samples were centrifuged at 1,000 G for 10 min twice.…”
Section: Methodsmentioning
confidence: 99%
“…This assay has been previously shown to correlate with the SARS CoV-2 90% plaque reduction neutralization test titer assay ( 24 ). We modified this assay as described previously to work with human milk ( 6 ). In brief, human milk was mixed with an equal volume of horseradish peroxidase conjugated to recombinant SARS CoV-2 RBD protein and incubated at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutralizing activity was seen in 83.3%, 70.4%, and 25.0% of milk samples at 1, 3, and 6 months post-vaccination. This study also showed that human milk samples showed similar IgG and neutralizing activity pre- and post-pasteurization, suggesting that also donor milk may confer passive immunization [ 107 ]. Recently, another prospective study compared IgA and IgG response and neutralizing activity against SARS-CoV-2 in human milk between lactating and vaccinated women out to 90 days after infection or vaccination.…”
Section: Breastfeeding and Infectionsmentioning
confidence: 98%